The Service Agile Supply Chain Information System Model for ASEAN University Network Quality Assurance at Institution Level - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research title The service agile Supply chain information system model for ASEAN University Network Quality Assurance at institution level. The objectives of research to study the model and to study method including, to assess The service agile Supply chain information system model for ASEAN University Network Quality Assurance at institution level. A sample group consisted of ten in field of 5 expert in supply chain ,two expert in information system and three experts in the field Quality Assurance . All totalling ten experts. The research tool was questionnaire about The service agile Supply chain information system model for ASEAN University Network Quality Assurance at institution level. The findings reveal that The service agile Supply chain information system model for ASEAN University Network Quality Assurance at institution level is consisted of five key elements which are 1) main elements 2) suppliers /services 3) university 4) customers 5)consumer. The model development process has 5 components that This model develop to information system .As the overall model was shown at a very good level, the experts agreed.